2004
DOI: 10.1037/0022-3514.87.6.926
|View full text |Cite
|
Sign up to set email alerts
|

On the Selective Relation of Frontal Cortical Asymmetry and Anger-Out Versus Anger-Control.

Abstract: The model of anterior asymmetry and emotion proposes an asymmetric representation of approach and withdrawal systems in the left and right anterior brain regions. Within this framework, 3 different concepts have been related to anterior asymmetry: affective valence, motivational direction, and behavioral activation. The aim of the present study was an empirical investigation into the relation between anterior cortical activity and questionnaire measures related to the 3 dimensions positive versus negative affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
128
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 80 publications
24
128
5
Order By: Relevance
“…This pattern was later conceptually replicated by Hewig, Hagemann, Seifert, Naumann, and Bartussek (2004) and by Rybak, Crayton, Young, Herba, and Konopka (2006). Harmon-Jones (2004) later confirmed that this pattern is not attributable to any positive feelings about anger among people high in trait anger.…”
Section: Hemispheric Activation Affect and Motivational Directionmentioning
confidence: 67%
“…This pattern was later conceptually replicated by Hewig, Hagemann, Seifert, Naumann, and Bartussek (2004) and by Rybak, Crayton, Young, Herba, and Konopka (2006). Harmon-Jones (2004) later confirmed that this pattern is not attributable to any positive feelings about anger among people high in trait anger.…”
Section: Hemispheric Activation Affect and Motivational Directionmentioning
confidence: 67%
“…The frontal cortex was found to be asymmetrically involved in the expression of positive/negative emotions related to approach/withdrawal motivational behaviors (Harmon-Jones et al, 2006). In particular, a left-lateralized increase of resting-state frontal activation was correlated with higher externalized anger, a negative but approach-oriented emotion (Harmon-Jones et al, 2003;Carver, 2004;Hewig et al, 2004). The rightward connectivity asymmetry found in DMN frontal regions can be consistent with the abovementioned findings, suggesting that the persistent engagement of the left frontal cortex could prevent frontal regions from normally interacting with the rest of the DMN, resulting in a modified resting-state connectivity pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during social conditioning No and Yes are universally used as feedback words. Saying No to oneself as internal feedback is of particular relevance to activity of the OFC since it is a common form of inner cognitive feedback affecting self control, which presumably is modulated by OFC function (Bechara, Damasio, & Damasio, 2000).Underlying social conditioning, the perception of Yes and No probably relate to approach/ avoidance and behavioral activation (BAS)/inhibition (BIS) systems (Hewig et al, 2004). Behavioral preferences triggering BIS in particular may have a role in one's sensitivity to reinforcement contingencies (Gray & McNaughton, 1996).…”
mentioning
confidence: 99%
“…(Goldstein et al, 2005). However, healthy variability in the successful control of anger have only recently drawn attention (Hewig, Hagemann, Seifert, Naumann, & Bartussek, 2004). …”
mentioning
confidence: 99%
See 1 more Smart Citation